Towards Exploring New Chinese Migrant Businesses in Auckland, New Zealand: A Multi-Method Research (London Journal of Research In Humanities and Social Sciences, 2026)
With three decades of embracing a neoliberal immigration policy in New Zealand, the number of the China-born new migrants has grown significantly in the country. Consequently, businesses run by these new Chinese migrants have contributed significantly to the country’s economy and are an integral part of the country’s urban economic landscape. However, research on their entrepreneurship remains limited. This research aims to use multiple methods to examine the entrepreneurial activities of this group of migrants in Auckland, New Zealand, focusing on business types, industry sectors, and factors that drive their business choices from the macro, meso, and micro perspectives. Data from Skykiwi Orange Page, Chinese Herald, and interviews with 29 new Chinese migrant business owners reveals concentrations in Retail Trade, Professional Services, and Construction, influenced by personal interests, market demand, and experience.
Keywords: china; ethnic entrepreneurship; new Chinese migrant businesses; New Zealand; transnational migrant entrepreneurship; transnational migration